Original sin - Brennan, Allison (Brennan, Allison. Seven deadly sins., 2010)
"Haunted by chilling memories of demonic possession and murder, Moira O'Donnell has spent seven years hunting down her mother, Fiona, whose command of black magic has granted her unprecedented control of the underworld. Now Moira's global search has led her to a small California town that's about to become hell on earth. Tormented by his own terrifying past and driven by powers he can't explain, ex-seminarian Rafe Cooper joins Moira's dangerous quest. But Fiona is one devilish step ahead. Hungry for greater power, eternal youth, and stunning beauty, the sorceress is unleashing upon the mortal world the living incarnations of the Seven Deadly Sins. Together with a demonologist, a tough female sheriff, and a true-crime writer chasing the ultimate story, Moira and Rafe are humanity's last best chance to snatch salvation from the howling jaws of damnation."-p.[4] of cover.